2014
DOI: 10.1186/1471-2296-15-66
|View full text |Cite
|
Sign up to set email alerts
|

Finding a BETTER way: A qualitative study exploring the prevention practitioner intervention to improve chronic disease prevention and screening in family practice

Abstract: BackgroundOur randomized controlled trial (The BETTER Trial) found that training a clinician to become a Prevention Practitioner (PP) in family practices improved chronic disease prevention and screening (CDPS). PPs were trained on CDPS and provided prevention prescriptions tailored to participating patients. For this embedded qualitative study, we explored perceptions of this new role to understand the PP intervention.MethodsWe used grounded theory methodology and purposefully sampled participants involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…While this study also confirmed what we learned from the qualitative study associated with the BETTER trial, namely, that introducing the new role of a PP changed dynamics in primary care settings for patients, the primary care team, and other primary care providers [7], it also explored contextual nuances and shed light on different perspectives related to the implementation in a different primary care setting. Early engagement facilitated program uptake and improved the ability to better adapt the program to the needs of the participants.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…While this study also confirmed what we learned from the qualitative study associated with the BETTER trial, namely, that introducing the new role of a PP changed dynamics in primary care settings for patients, the primary care team, and other primary care providers [7], it also explored contextual nuances and shed light on different perspectives related to the implementation in a different primary care setting. Early engagement facilitated program uptake and improved the ability to better adapt the program to the needs of the participants.…”
Section: Resultssupporting
confidence: 73%
“…The unique characteristic of BETTER is the comprehensive approach used to address a wide variety of maneuvers related to a patient’s health, such as blood results, diet, physical activity, mental health, in a one-hour prevention visit with a PP [6, 7]. While this qualitative study suggests that the implementation of BETTER 2 was valued as an opportunity to address patients’ complex and multi-faceted health care needs from a CDPS perspective, it also revealed important barriers related to implementing comprehensive preventive activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working to build understanding of roles and shared leadership is also widely attributed to enhancing collaboration (58,60,61,65). There is also evidence of the value of interprofessional education (67,77). Intentional, team-focused activities, including formal meetings, professional development programs, social activities, and retreats, are essential to sustaining and building relationships needed for highly functioning teams (75,78).…”
Section: Team Functionmentioning
confidence: 99%
“…Finally, in the light of decreasing numbers of GPs it is crucial to invite medical practice assistants and practice nurses to join training courses and to implement counseling in collaboration with the GP and under his/her responsibility [33,34]. In our program "Health coaching" we recently started this initiative.…”
Section: Itemmentioning
confidence: 99%